Recepcja socjologii światowej w lwowskiej kolebce 150-letniej socjologii polskiej = The reception of world sociology in the Lviv cradle of 150-year-old Polish sociology - Fryszkowska, Viktorija; Kosiński, Stanisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper discusses the reception of world sociology in the Lviv circle of Polish sociologists at the turn of the 19th and 20th centuries, which was co-formed by diverse professionals, especially lawyers and economists. This phenomenon was primarily shown in the publications by Jozef Supiński (1804-1893) - the honorary father of Polish sociology (which can be traced back to 1860), by Bolesław Limanowski (1835-1935) - a historian of social thought, and by Władysław Pilat (1857-1909) - a lawyer and also a painter.
Keywords: socjologia polska; Lwów